A preliminary study on the mechanism of the Liangzhu culture’s migration across the Yangtze river - Xiao, Jiayi; Shang, Zhiyuan; Zhang, Zixin; Xiao, Shengjun; Jia, Xin (Frontiers in Earth Science, 2023)
The Liangzhu (5300–4200 cal BP) were the most famous of the Neolithic cultures who settled near the lower reaches of the Yangtze River in China. They were mainly found from Shanghai in the east to the Ningzhen Mountains in the west, and from the Qiantang River basin in the south to the Huanghuai plain in the north. They originated in the area around Taihu Lake, located on the south bank of the Yangtze River delta. Recently, a considerable number of large-scale Liangzhu cultural sites have been found in the Jianghuai and Huanghuai regions north of the Yangtze River. Exactly how the Liangzhu crossed the Yangtze River is a hot topic, and archaeologists currently believe that the Liangzhu used two several main possible migration routes. One would have crossed the Zhenjiang area, while another the other would have started near the estuary of the Yangtze River before moving north along the ancient coastline to the Jianghuai region during the later Liangzhu period of the Liangzhu culture, or crossed the Yangtze River from the east of present Grand Canal to Jianghuai and Huanghuai. Based on how the Yangtze River delta formed during the Holocene and the evolution of the estuarine sand bar, this route is considered the most feasible and was probably the main route the Liangzhu used for migrating across the Yangtze River in today’s Changzhou–Jiangyin–Zhangjiagang belt.